Klasifikasi Kualitas Susu Sapi Menggunakan Metode Support Vector Machine (SVM) - Puspita Sari; Lailil Muflikhah; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Cow milk has a lot of animal protein and have benefit for children and whoever in process for grow up. Cow milk contains good essential amino acids. Malang Animal Health Laboratory as the unit executor in east java Animal Husbandry Department do a test in kesmavet for efforts to secure milk as a farm product with appropriate testing in suitable with the Indonesian National Standard (SNI). The classification of cow milk quality is still using organoleptic (smell, taste, color) that are linguistic, so that variable and parameter are uncertain and become themain obstacle of expert in determining good milk quality. To resolve this issue, this can be done with schizophrenia classification using support vector machine (SVM) algorithm, which SVM performace is more suitable than other classification methods. In this study there are 269 data that is divided into two data that is data training and data testing with three classification result, that is low, medium, and hight. The result in this paper get the best acuracy based ratio data 50%:50%, with Kernel RBF and Î» (lambda) = 0,001, C (complexity) = 0,01, Î³ (gamma) =0,00001, maximum iteration = 30 and Ïƒ kernel RBF= 2. The average result of accuracy using SVM method in cow milk quality classification was 92.82% and highest accuracy was 94.02%.